2008
DOI: 10.4161/cbt.7.8.6263
|View full text |Cite
|
Sign up to set email alerts
|

JSI-124 inhibits glioblastoma multiforme cell proliferation through G2/M cell cycle arrest and apoptosis augmentation

Abstract: JSI-124 (cucurbitacin I) is a selective inhibitor of Janus kinase/signal transducer and activator of transcription 3(JAK/STAT3) and has been shown to exert anti-proliferative and anti-tumor properties both in vitro and in vivo. As STAT3 activation has been implicated in the development of glioma, we investigated the therapeutic efficacy of JSI-124 on glioblastoma multiforme (GBM) by interfering with STAT3 pathway. In present study, two GBM cell lines, U251 and A172 cells, were treated with JSI-124. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 28 publications
(52 reference statements)
5
63
0
Order By: Relevance
“…The IC 50 values of cucurbitacin I against U251 and T98MG cells were 170 and 245 nM, respectively. Treatment with cucurbitacin I resulted in growth inhibition of U251 and T98G cells in a dose-dependent manner, but their responses varied (Fig.…”
Section: Cucurbitacin I Inhibited the Growth Of Gbm Cells In Vitro Anmentioning
confidence: 97%
“…The IC 50 values of cucurbitacin I against U251 and T98MG cells were 170 and 245 nM, respectively. Treatment with cucurbitacin I resulted in growth inhibition of U251 and T98G cells in a dose-dependent manner, but their responses varied (Fig.…”
Section: Cucurbitacin I Inhibited the Growth Of Gbm Cells In Vitro Anmentioning
confidence: 97%
“…Cucurbitacin I, also known as elatericin B, is a member of a family of natural occurring compounds with potent antitumor activity in many human cancers, including glioblastoma, adenocarcinoma of the lung and breast cancer cells (11)(12)(13). The cucurbitacin family comprises a group of triterpenoid compounds originally isolated from the plants of the Cucurbitaceae family.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these anticancer compounds have been observed in many plant families, including Cruciferae, Cucurbitaceae and Scrophulariaceae, and have been used as traditional or folk medicines for centuries in China, India, Brazil and Peru (13,14). Previous studies have demonstrated that cucurbitacin I inhibits the JAK/STAT3 pathway in a number of cancer cell lines and in vivo tumor models (11,15). Upon inhibition of STAT3-dependent gene transcription, cucurbitacin I elicits antiproliferative effects in glioma, lung and breast cancer cells with activated STAT3 (13,16).…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is the most common and most virulent primary brain tumor in adults and accounts for at least 80% of malignant gliomas (1,2). Over 12,000 patients die because of primary brain tumor in United States every year.…”
Section: Introductionmentioning
confidence: 99%